New methodological approaches in the anthropological demography of Romani groups : An example from the study of the evolution of the infant and child mortality of the Gitanos or Calé of Spain (1871-2007) - Gamella, Juan F.; Quesada Garrido, Alejandro; Carrasco-Muñoz, Elisa Martín (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2017)
Probably the most important change that affected the Gitano people of Spain in its recent history has been the rapid decline in their infant and child mortality patterns. There is however an almost complete absence of studies on this process. Data is difficult to obtain, as ethnic affiliation is usually not recorded in parish or civil records, and the base population is generally unknown. In this paper we will describe the methods we followed to overcome those problems in the genealogical and family reconstitution of the Gitano population of 22 contiguous localities of Andalusia, which includes data on over 19,000 people. From this database we produced annual time series that show a differentiated model of mortality decline occurring between 1950 and 1975.